2015
DOI: 10.1128/aac.00872-15
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole Enhances the Osteogenic Activity of Human Osteoblasts In Vitro through a Fluoride-Independent Mechanism

Abstract: b Periostitis, which is characterized by bony pain and diffuse periosteal ossification, has been increasingly reported with prolonged clinical use of voriconazole. While resolution of clinical symptoms following discontinuation of therapy suggests a causative role for voriconazole, the biological mechanisms contributing to voriconazole-induced periostitis are unknown. To elucidate potential mechanisms, we exposed human osteoblasts in vitro to voriconazole or fluconazole at 15 or 200 g/ml (reflecting systemic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…There is no recommendation for measuring the bone‐specific alkaline phosphatase level to identify at‐risk patients who may develop periostitis. There also is no reported association between periostitis and the levels of bone‐specific alkaline phosphatase in patients taking voriconazole . While serum fluoride levels may be used as surrogate markers for periostitis in symptomatic patients when a bone scan is not readily available, they are not widely available, hence delaying the diagnosis .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no recommendation for measuring the bone‐specific alkaline phosphatase level to identify at‐risk patients who may develop periostitis. There also is no reported association between periostitis and the levels of bone‐specific alkaline phosphatase in patients taking voriconazole . While serum fluoride levels may be used as surrogate markers for periostitis in symptomatic patients when a bone scan is not readily available, they are not widely available, hence delaying the diagnosis .…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have shown that fluoride exposure causes aberrant activation of osteoblasts and inhibits osteoclast‐mediated bone resorption . Voriconazole promotes osteoblastic differentiation through 2 pathways, either by increasing alkaline phosphatase or by promoting the expression of runx2, a key protein associated with osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutaneous malignancy has not been recognized to date, and hyperfluorosis with isavuconazole is unlikely given the differences in chemical structure between voriconazole and isavuconazole and that this phenomenon does not appear to be a class-effect. 67 …”
Section: Introductionmentioning
confidence: 99%
“…Bony changes resemble periostitis deformans, a condition associated with drinking excessively fluoridated water [1][2][3] . Additionally, voriconazole is believed to cause bony changes in a nonfluoride mediated pathway via osteoblast activation and stimulation of cytokine release 4 . In our patient, voriconazole was replaced with posaconazole and he experienced significant improvement within weeks of this change.…”
mentioning
confidence: 99%